Cocos Island (Pacific of Costa Rica) coral reefs after the 1982-83 El Niño disturbance - Guzmán, Héctor M (Universidad de Costa Rica, 1992)
Cocos Island coral reefs were adversely affected by tbe 1982-83 El Niño warming event. Surveys made in 1987 indicated dramatic coral mortality at aH depths (l -24m). Live coral cover on tbree studied coral reefs was 2.6, 2.9 and 3.5%. Population den sities of the corallivores Acanthaster planci and Arothron meleagris were relatively high witb tbeir feeding activities concentrated on tbe few surviving colonies. Density of Diadema mexicanum was also high, being responsible for tbe eros ion of large reef framework areas. It is predicted that recovery of the original reef-framework tbickness is in tbe order of centuries.